The Role of Adaptation Technology to enhance Social and Economic Resilience to Climate Change - Marsal, Antonino Pedro; Oluwatosin, Adebayo; Sulani, Sulani (Metromedia, 2024)
Climate change has had a significant impact on various sectors of life, requiring the development and implementation of adaptation technology as a strategic solution. This research aims to analyze the role of adaptation technology to deal with climate change and its impact on the social and economic life of the community. Using a literature research approach, this research explores the challenges in the development of adaptation technology, the effectiveness of implementation in various sectors, and its contribution to social and economic resilience. The results show that adaptation technologies play an important role in enhancing the productivity of the agricultural sector, strengthening infrastructure against natural disasters, and creating adaptive financial systems to reduce economic risks due to climate change. Adaptation technologies also contribute to raising community awareness of climate change risks and supporting sustainable development policies. Challenges in the implementation of these technology are still great, including limited funding, gaps in access to technology, and lack of policy coordination between central and local governments. More effective strategies are needed to accelerate the adoption of adaptation technology through enhanced investment in research and development, integration of ecosystem-based policy, and active community participation in adaptation planning. With a more inclusive and evidence-based approach, it is expected that adaptation technology can provide more optimal solutions to the challenges of climate change and improve the social and economic resilience of the community